2001
DOI: 10.1039/b104123c
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the primary structure of the polypeptide catalyst on the enantioselectivity of the Juliá–Colonna asymmetric epoxidation of enones

Abstract: Epoxidation of chalcone (1), using basic hydrogen peroxide, catalysed by polypeptides with defined primary structures demonstrates that the residues in the chain near to the N-terminus determine the stereochemical outcome of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Later, when Roberts investigated the role of the amino acid at the N-terminus of the catalyst [66], it was shown that those residues close to the N-terminus of the chain determined the sterochemical outcome of the oxidation. If the amino acids in the oligomers were changed and tested in the epoxidation of trans-chalcone 1c, the penultimate and penultimate-plus-one residues were shown to play a crucial role.…”
Section: Polyamino Acidsmentioning
confidence: 99%
“…Later, when Roberts investigated the role of the amino acid at the N-terminus of the catalyst [66], it was shown that those residues close to the N-terminus of the chain determined the sterochemical outcome of the oxidation. If the amino acids in the oligomers were changed and tested in the epoxidation of trans-chalcone 1c, the penultimate and penultimate-plus-one residues were shown to play a crucial role.…”
Section: Polyamino Acidsmentioning
confidence: 99%
“…Immobilization of the poly(amino acid) on silica had been already described by Roberts and provided the optimum heterogeneous catalyst in terms of efficiency, stability and ease of recycling. 18 ð2Þ…”
Section: A Enantioselective C-o Bond Forming Catalystsmentioning
confidence: 99%
“…3,7 Although the diastereoselective epoxidation of electron-rich alkenes by these two oxidants is well documented, 8 the reaction of electron-poor substrates remains a synthetic challenge. 9 Urea-hydrogen peroxide (UHP) is both cheap and safe, yielding an innocuous byproduct in oxidation reactions. It has the advantages of being relatively stable and more convenient in use than aqueous hydrogen peroxide.…”
mentioning
confidence: 99%